A STUDY ON GRANGER CAUSAL RELATIONSHIP BETWEEN MACROECONOMIC VARIABLES AND STOCK PRICE BEHAVIOR: EVIDENCE FROM INDIA - Shelly, Dr. Richa; Kumar katuri, Dr. Phani; Sekhar, Dr. B.M.Raja (The journal of contemporary issues in business and government, 2022)
In this study, we use multivariate stepwise regression analysis to examine how various macroeconomic factors have affected the Indian stock market. To investigate the underlying dynamic causal relationship between the variables,a Granger causality test was performed and Average monthly closing prices of BSE Sensex and S&P CNX Nifty are used as dependent variables, while industrial production (IIP), wholesale price index (WPI), money supply (M3), interest rates (IR), trade deficit (TD) and investment are institutional variables. Foreign exchange (FII), exchange rate (ER), crude oil price (CP), and gold price (GP) are used as independent variables (GP).Data from January 2020 through June 2022 was evaluated for this analysis. The empirical findings of this study feature the significance of macroeconomic factors in explaining the behavior of the Indian stock market. Investors' inclination for gold has to be tempered, and the government should instead encourage further participation in the stock market.